1997
DOI: 10.1006/dbio.1997.8592
|View full text |Cite
|
Sign up to set email alerts
|

Neuroepithelial Stem Cells from the Embryonic Spinal Cord: Isolation, Characterization, and Clonal Analysis

Abstract: Adherent cultures of E10.5 rat neuroepithelial cells (NEP cells) from the caudal neural tube require FGF (fibroblast growth factor) and CEE (chick embryo extract) to proliferate and maintain an undifferentiated phenotype in culture. Epidermal growth factor (EGF) does not support E10.5 NEP cells in adherent culture and NEP cells do not form EGF-dependent neurospheres. NEP cells, however, can be grown as FGF-dependent neurospheres. NEP cells express nestin and lack all lineage-specific markers for neuronal and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
176
1
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 271 publications
(190 citation statements)
references
References 57 publications
(23 reference statements)
10
176
1
1
Order By: Relevance
“…The number of GFAP-positive cells increased along the differentiation process, representing 8.9±0.3% on Day 2, 75.9±6.0% on Day 4, and 86.5± 0.8% of total cells on Day 8. This observation coincides well with a previous report (Kalyani et al, 1997), in which GFAP-positive cells constituted the largest portion (73±6.0%) of the total population of differentiated neuroepithelial cells after 5 days of differentiation.…”
Section: Verification Of Spinal Cord Precursor Cells Into Neuronal Cesupporting
confidence: 93%
“…The number of GFAP-positive cells increased along the differentiation process, representing 8.9±0.3% on Day 2, 75.9±6.0% on Day 4, and 86.5± 0.8% of total cells on Day 8. This observation coincides well with a previous report (Kalyani et al, 1997), in which GFAP-positive cells constituted the largest portion (73±6.0%) of the total population of differentiated neuroepithelial cells after 5 days of differentiation.…”
Section: Verification Of Spinal Cord Precursor Cells Into Neuronal Cesupporting
confidence: 93%
“…Thus, our results suggest the common control mechanisms for adult and embryonic progenitors. Neural stem cells are present in both the adult and embryonic spinal cord (Weiss et al, 1996;Kalyani et al, 1997;Johansson et al, 1999;Shihabuddin et al, 2000). We also identified bipotential progenitors in our cultures, although it was not determined whether these cells possessed the properties of bona fide stem cells.…”
Section: Molecular Properties Of Adult Neural Progenitorsmentioning
confidence: 86%
“…In addition, in vivo overexpression and BMP receptor truncation studies have shown a similar role for BMP in promoting neuronal differentiation at the expense of cell proliferation in the VZ (W. . From early work on VZ stem/precursor cell cultures from the telencephalon (Murphy et al, 1990;Kilpatrick and Bartlett, 1993) and neural tube (Kalyani et al, 1997), FGF-2 was found to be critical in maintaining proliferation and an undifferentiated state. Although there is expression in the VZ of all 4 FGF receptors in vivo (Bansal et al, 2003;Reid and Ferretti, 2003), neural stem/precursor cells derived from the rat neural tube uniquely express FGFR4 (Kalyani et al, 1999).…”
Section: Similarities and Differences Between Adult And Fetal Neural mentioning
confidence: 99%